PENGARUH MODEL PEMBELAJARAN SAVI TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 2 ATU LINTANG KABUPATEN ACEH TENGAH - Fatimah Fatimah; Intan Safiah; Suci Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of the SAVI (Somatic, Auditory, Visualization, Intellectual) learning model on the science and social studies (IPAS) learning outcomes of fifth-grade students at SD Negeri 2 Atu Lintang, Central Aceh Regency. This study employed a quantitative approach with a pre-experimental research design using a one-group pretest-posttest design. The sample consisted of 24 fifth-grade students selected through a total sampling technique. Data were collected through pretest and posttest instruments. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the paired sample t-test assisted by IBM SPSS Statistics Version 27 for Windows. The results showed that the average pretest score was 48.33 and increased to 81.04 on the posttest. The paired sample t-test yielded a significance value (2-tailed) of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the SAVI learning model significantly affects the IPAS learning outcomes of fifth-grade students at SD Negeri 2 Atu Lintang, Central Aceh Regency.